Driving Behavior Factors of Young Drivers Influencing Motorcycle Traffic Accidents in Jember, East Java - Intan N. Baharini; Hera Widyastuti (Institut Teknologi Sepuluh Nopember (ITS), 2024)
Traffic accidents are unexpected and undesirable incidents that occur on the highway, resulting in damage and casualties. Traffic accidents occur due to several contributing factors, including driver behavior, road conditions, technical errors in vehicles, and environmental conditions. Based on several studies, motorcycles are the vehicles most frequently involved in traffic accidents. Jember is one of the districts in East Java with a high number of motorcycle accidents. Based on data from 2017 to 2019, motorcycle traffic accidents in Jember reached 3,543 cases. Most of motorcycle riders involved in accidents in Jember are young riders. Young riders are considered to lack proper driving attitudes. This study was conducted to determine the relationship between driving behavior and accidents in Jember District among young motorcycle riders using structural equation modeling (SEM). The primary data used were survey results with respondents consisting of motorcycle riders aged up to 24 years old residing in Jember District. There is also supporting data in the form of accident data that occurred in Jember District from 2018 to 2022. Using that method, the results showed that driving behavior variables significantly influencing traffic accidents are traffic violations and stunts. The traffic violations variable has an influence of 0.840. Meanwhile, the stunts variable has an influence of 0.267.